The Relevance of the Equator Monument as a Representation of Pontianak City Identity - Bayuardi, Galuh; Equanti, Dian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The Equator Monument is a well-known landmark of Pontianak City. The city identity is related to the sense of place when someone is in that place. The sense of place acknowledges the subjective individual city imagery. From this point of view of citizen subjectivity, this study aimed to explain how the Khatulistiwa Monument represents the identity of Pontianak City, and how is the production of space in the Khatulistiwa Monument area. This study used a qualitative research method. It collected data from Z-generation citizens and field observation. The results of this study show that the Khatulistiwa Monument is still relevant to the identity of Pontianak City due to its popularity, but the Khatulistiwa Monument area did not fulfil the sense of place that represents the of Pontianak City’s identity. The production of space of The Khatulistiwa Monument was made of the activities of its visitors who perceive it, entrepreneurs who use the space, and the Tourism Office that designed TheKhatulistiwa Monument area.